Research for an enhanced fault-tolerant solution against the current sensor fault types in induction motor drives - Tran, C. D.; Kuchar, M.; Nguyen, P. D. (Національний технічний університет "Харківський політехнічний інститут", 2024)
Recently, three-phase induction motor drives have been widely used in industrial applications; however, the feedback signal failures of current sensors can seriously degrade the operation performance of the entire drive system. Therefore, the motor drives require a proper solution to prevent current sensor faults and improve the reliability of the motor drive systems. The novelty of the proposed research includes integrating the current sensor fault-tolerant control (FTC) function according to enhanced technique into the field-oriented control loop for speed control of the motor drive system. Purpose. This research proposes a hybrid method involving a third difference operator and signal comparison algorithm to diagnose various types of current sensor faults as a positive solution to enhance the stability of the induction motor drive system. Methods. A hybrid method involving a third difference operator for the measured speed signals and a comparison algorithm between measured and estimated current signals are proposed to diagnose the current sensors’ health status in the fault-tolerant process. After determining the faulty sensor, the estimated current signals based on the Luenberger observer are used immediately to replace the defective sensor signal. Results. The current sensor is simulated with various failure types, from standard to rare failures, to evaluate the performance of the FTC method implemented in the MATLAB/Simulink environment. Simultaneously, a fault flag corresponding to a defective sensor should be presented as an indicator to execute the repair process for faulty sensors at the proper time. Practical value. Positive results have proven the feasibility and effectiveness of the proposed FTC integrated into the speed controller to improve reliability and ensure the stable operation of the induction motor drive system even under current sensor fault conditions.

Останнім часом трифазні приводи з асинхронними двигунами широко використовуються у промисловості; однак відмови сигналу зворотного зв'язку датчиків струму можуть погіршити експлуатаційні характеристики всієї системи приводу. Тому для електроприводів потрібне належне рішення для запобігання відмов датчиків струму та підвищення надійності систем приводу. Новизна пропонованого дослідження полягає в інтеграції функції відмовостійкого управління датчиком струму (FTC) відповідно до вдосконаленої методики в контур управління полем для управління швидкістю системи приводу. Мета. У цьому дослідженні пропонується гібридний метод, що включає оператор третьої різниці та алгоритм порівняння сигналів для діагностики різних типів відмов датчиків струму як позитивне рішення для підвищення стійкості системи приводу з асинхронним двигуном. Методи. Пропонується гібридний метод, що включає оператор третьої різниці для виміряних сигналів швидкості та алгоритм порівняння між виміряними та оціночними сигналами струму, для діагностики стану справності датчиків струму у відмовостійкому процесі. Після визначення несправного датчика сигнали оцінки струму на основі спостерігача Люенбергера негайно використовуються для заміни сигналу несправного датчика. Результати. Датчик струму моделюється з різними типами відмов, від стандартних до рідкісних відмов, з метою оцінки продуктивності методу FTC, реалізованого у середовищі MATLAB/Simulink. Одночасно прапорець несправності, що відповідає несправному датчику, повинен бути представлений як індикатор для виконання процесу ремонту несправних датчиків у належний час. Практична цінність. Позитивні результати довели здійсненність та ефективність пропонованого FTC, інтегрованого в регулятор швидкості, для підвищення надійності та забезпечення стабільної роботи системи приводу з асинхронним двигуном навіть в умовах несправності датчика струму.
Keywords: current sensor fault; estimated current; fault-tolerant control; field-oriented control; induction motor drive; несправність датчика струму; розрахунковий струм; відмовостійке керування; орієнтоване на поле керування; привід з асинхронним двигуном